Perencanaan Strategis Sistem Informasi SMKN 1 Garut Menggunakan Metode Anita Cassidy - Wawan Wiharya; Andriansyah Maulana; Ardhi Akmaludin Jadhira (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
SMK Negeri 1 Garut is a vocational high school in Garut Regency which is under the West Java provincial government which focuses on various fields of expertise. Business process activities at SMK Negeri 1 Garut require an information system in the form of an application in order to facilitate every activity in the academic environment of SMKN 1 Garut. SMK Negeri 1 Garut is aware of the need for a strategic planning of information systems to manage information systems for existing information systems and information systems to be built. Strategic planning has an important role in running a business process in an agency, one of which is an educational institution. Strategic planning of information systems with Anita Cassidy is one method to help develop business processes and information systems which has four phases, namely the visioning, analysis, direction, and recommendation phases. This research will produce a strategy document and an information system roadmap that is recommended for SMKN 1 Garut for the next five years by using supporting tools in obtaining decisions. Keywords — Strategic Planning, Anita Cassidy, Information Systems, SMKN 1 Garut